The Marriage of State Law and Individual Rights and a New Limit on the Federal Death Penalty - Ross, Jonathan (2014)
Since the 1990s, federal prosecutors have, with increasing frequency, sought the death penalty for federal offenses committed in and also punishable under the laws of non-death penalty states. Critics of this practice have pointed out that federal prosecutors can use the federal death penalty to circumvent a state's abolition of capital punishment. Courts, however, have almost unanimously rejected arguments that state law should be a shield from federal punishment for federal offenses. This article proposes a novel way to challenge the federal death penalty's use in a non-death penalty state—the Supreme Court's reasoning in United States v. Windsor. In Windsor, the Court held that federal interference with a state law right arising in an area traditionally regulated by states is subject to heightened scrutiny under the Due Process Clause. In some instances, Windsor precludes federal capital prosecutions. This article considers a Windsor-based motion to dismiss a notice of intent to seek the federal death penalty. The federal capital prosecution in a non-death penalty state interferes with a state law right to not be executed. As states have traditionally prosecuted violent murders, this right arises in an area traditionally regulated by states. Applying due process scrutiny, a court will ask whether a prosecutor's animus towards the state's lack of capital punishment motivated the prosecution in the first place, or whether there is an independent federal interest. If animus alone motivated the prosecution, then Windsor demands that the court reject the attempt to seek capital punishment